Therapeutic Group Therapy for Pregnant Women on Childbirth Readiness in the Kunciran Baru Health Center in Tangerang City - Lailatul Fadilah; Bangun Wijonarko (Politeknik Kesehatan Kementerian Kesehatan Banten, 2024)
Introduction: Pregnancy and childbirth have an important role because of their enormous influence on human growth and development. Although there have been efforts to improve maternal health through various government programs, these efforts have only touched the physical aspect and have not yet made efforts to improve the psychosocial and psychiatric aspects of pregnant women. This is important because the growth and cognitive and emotional development of children are closely related to the mother's psychiatric problems during pregnancy. One of the efforts that can be done is an information program to educate individuals with emotional problems to be able to maintain homeostasis against unexpected changes or events that occur gradually, helping members cope with stress in life, focusing on dysfunctions of feelings, thoughts, and behaviors known as Therapeutic Group Therapy. Method: This research design uses quasi-experiments. The study subjects were taken by quota sampling, the sample of this study was pregnant women in the Kunciran Baru Health Center area of Tangerang City. The number of samples was 24 people. Data analysis using T-dependent test. Results: the statistical test obtained a P value of 0.024 (P value ≤ 0.05), so it can be concluded that there is a significant difference between the average delivery readiness of the intervention group and the control group. Conclusion: it was concluded that there was a significant difference between the average delivery readiness of the intervention group and the control group.